Electronic Dance Music Launchpad Composer Android Application - Nur Hadisukmana; Ida Made Santika Kusuma Yogi (President University, 2018)
Music is the art of combining vocal or instrumental sounds or tones in varying melody, harmony, rhythm, and timbre. Music can come from any instruments, even there are many musician use household furniture to create a music. Nowadays, the development of music industry is much influenced by technology. One new genre music that emerge because of technology development is EDM. EDM is stand for Electronic Dance Music. EDM is a broad range of percussive electronic music genres produced largely for nightclubs, raves and festival. A lot of software, applications and tools were created to compose the sound to create EDM. Although these software are easy to install but most of these software are difficult to use and take time to learn it. What people need in this era are simplicity, portability, user friendly and easy to use.